2013
DOI: 10.1016/j.ultrasmedbio.2013.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Intracellular Delivery of a Model Drug Using Microbubbles Produced by a Microfluidic Device

Abstract: Focal drug delivery to a vessel wall facilitated by intravascular ultrasound and microbubbles holds promise as a potential therapy for atherosclerosis. Conventional methods of microbubble administration result in rapid clearance from the blood stream and significant drug loss. To address these limitations, we evaluated whether drug delivery could be achieved with transiently stable microbubbles produced in real-time and in close proximity to the therapeutic site. Rat aortic smooth muscle cells were placed in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 52 publications
2
43
0
Order By: Relevance
“…Mediated delivery was one kind of assistant measurements for supporting the ultrasound gene or drug transfer process (Koike et al 2005;Wang et al 2008). Intracellular delivery had been extensively applied in short interfering RNA (siRNA) or drug delivery by microbubble-enhanced ultrasound Hynynen 2005a, 2005b;Dixon et al 2013). Nevertheless, the object delivery and delivery pathways are close interaction with each other and aim at eliminating cancer or illness.…”
Section: Hot Issues and Future Trendsmentioning
confidence: 99%
“…Mediated delivery was one kind of assistant measurements for supporting the ultrasound gene or drug transfer process (Koike et al 2005;Wang et al 2008). Intracellular delivery had been extensively applied in short interfering RNA (siRNA) or drug delivery by microbubble-enhanced ultrasound Hynynen 2005a, 2005b;Dixon et al 2013). Nevertheless, the object delivery and delivery pathways are close interaction with each other and aim at eliminating cancer or illness.…”
Section: Hot Issues and Future Trendsmentioning
confidence: 99%
“…This work however cannot determine if sonoporation occurred in these ex vivo arteries because the experiments were conducted at room temperature. However, other research has demonstrated that at comparable pressures and frequencies, sonoporation can be induced in vitro [53]–[55]. Future studies using in vitro and in vivo models may be performed to verify that sonoporation is induced by this system.…”
Section: Discussionmentioning
confidence: 94%
“…11,28,29 The insonation pulse applied to the transducer consisted of a displacement pulse and/or a burst pulse (1 or 2 MPa) based on previously investigated ultrasound conditions. 13,44,47 The displacement pulse was a long (500 cycle), high duty cycle (50%), low peak negative pressure (PNP = 600 kPa) pulse to displace microbubbles from flow to the vessel wall. The burst pulse was a short (50 cycle), low duty cycle (1%), high peak negative pressure (PNP = 1 or 2 MPa) pulse designed to disrupt microbubbles and induce drug release and uptake by cells.…”
Section: Methodsmentioning
confidence: 99%